2023
DOI: 10.2147/idr.s392908
|View full text |Cite
|
Sign up to set email alerts
|

Resistance and Molecular Characteristics of Methicillin-Resistant Staphylococcus aureus and Heterogeneous Vancomycin-Intermediate Staphylococcus aureus

Abstract: To investigate the molecular epidemiology of Staphylococcus aureus (S. aureus) isolated from patients in the Yellow River Delta region and to construct antibiotic resistance profiles in different genetic backgrounds. Methods: Antibiotics susceptibility testing, staphylococcal protein A (spa) typing and accessory gene regulator (agr) typing were performed for all the 204 strains. Isolates with the positive mecA gene and heterogeneous vancomycin-intermediate S. aureus (hVISA) were subjected to multilocus sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Moreover, there is a growing concern due to the increasing prevalence of hVISA in recent years. Shen et al identified 7.6% (36/476) hVISA among S. aureus isolated in 2010–2011 [ 73 ], while Liang et al discovered 10.8% (22/204) hVISA among isolates from inpatients and outpatients in 2019–2021 [ 74 ]. With the recent decrease in MRSA isolation rates, the proportion of MRSA among VISA/hVISA has also declined [ 73 , 74 ].…”
Section: Staphylococcus Aureusmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, there is a growing concern due to the increasing prevalence of hVISA in recent years. Shen et al identified 7.6% (36/476) hVISA among S. aureus isolated in 2010–2011 [ 73 ], while Liang et al discovered 10.8% (22/204) hVISA among isolates from inpatients and outpatients in 2019–2021 [ 74 ]. With the recent decrease in MRSA isolation rates, the proportion of MRSA among VISA/hVISA has also declined [ 73 , 74 ].…”
Section: Staphylococcus Aureusmentioning
confidence: 99%
“…Shen et al identified 7.6% (36/476) hVISA among S. aureus isolated in 2010–2011 [ 73 ], while Liang et al discovered 10.8% (22/204) hVISA among isolates from inpatients and outpatients in 2019–2021 [ 74 ]. With the recent decrease in MRSA isolation rates, the proportion of MRSA among VISA/hVISA has also declined [ 73 , 74 ]. Liang et al reported 22.7% of hVISA isolates belonged to ST72 and CC5 (ST5/965/7197), followed by CC59 (ST59) and ST25 (18.2%, respectively), which indicated that previous dominant hVISA/VISA clone ST239 in China is changed [ 74 ].…”
Section: Staphylococcus Aureusmentioning
confidence: 99%
See 1 more Smart Citation